Comprehension and application of learning strategies at self-regulated learning in elementary school students - Sonja Pečjak; Katja Košir (Psihološka Obzorja, 2003)
The main aim of the article is to show the connection between the comprehension and application of learning strategies in self-regulated learning in elementary school students. We would also like to show the connection between the comprehension and application of learning strategies and age, sex and school efficiency. The theoretical framework for the research is the four component model of self-regulative learning by B. Hofer, S. Yu and Pintrich (1998). We have focused on the first part of the model, which is about cognitive structure and cognitive strategies. The results of our research show that fifthgraderes use cognitive strategies before reading more often than seventhgraders. Girls use learning strategies more often than boys, particularly the strategies between and after reading. There are no significant differences in application of learning strategies between pupils with different school achievement. On the basis of the results of this research we also discuss possible educational implications.